FACTORS THAT EFFECT SALES VOLUME DURING THE COVID-19 PANDEMIC AT SUB-SECTORS COMPANIES OF COSMETICS AND HOUSEHOLD - Novianti, Helen (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
This study aims to analyze the factors that affect sales volume during the COVID-19 pandemic in cosmetics and household goods sub-sector companies listed on the BEI. This research uses quantitative data method and the source data is secondary data. The population in this study was 7 companies in the cosmetics and household sub-sectors. The sample in this study used purposive sampling with the sample criteria used in this study were companies that reported complete financial statements and used rupiah currency. Data analysis and testing consisted of descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (t-test) and simultaneously (F test), and coefficient of determination test. The test results from the t-test of the Promotional Cost variable have no and no significant effect on Sales Volume and the Production Cost variable has a significant effect on Sales Volume. The test results from the F test of Promotional Costs and Production Costs variables have a significant and significant effect on Sales Volume.